(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article cites the emergence and application of the term communicative competence, as well as ideas about the role and importance, goals of communicative competence in students in the process of teaching the Uzbek language. At the same time, the opinions of scientists were added.